A diet rich in C 3 plants reveals the sensitivity of an alpine mammal to climate change - Sabuj Bhattacharyya; Deborah A. Dawson; Helen Hipperson; Farah Ishtiaq (Molecular Ecology, 2019)
Plant–herbivore interactions provide critical insights into the mechanisms that govern the spatiotemporal distributions of organisms. These interactions are crucial to understanding the impacts of climate change, which are likely to have an effect on the population dynamics of alpine herbivores. The Royle's pika ( Ochotona roylei , hereafter pika) is a lagomorph found in the western Himalaya and is dependent on alpine plants that are at risk from climate change. As the main prey of many carnivores in the region, the pika plays a crucial role in trophic interactions. We examined topographical features, plant genera presence and seasonal dynamics as drivers of the plant richness in the pika's diet across an elevational gradient (2,600–4,450 m). We identified 79 plant genera in the faecal pellets of pikas, of which 89% were forbs, >60% were endemic to the Himalaya, and 97.5% of the diet plant genera identified followed the C 3 photosynthetic pathway. We found that, during the premonsoon season, the number of genera in the pika's diet decreased with increasing elevation. We demonstrate that a large area of talus supports greater plant diversity and, not surprisingly, results in higher species richness in the pika's diet. However, in talus habitat with deep crevices, pikas consumed fewer plant genera suggesting they may be foraging suboptimally due to predation risk. The continued increase in global temperature is expected to have an effect on the distribution dynamics of C 3 plants and consequently influence pika diet and distribution, resulting in a significant negative cascading effect on the Himalayan ecosystem.